Middle Class China. Identity and Behaviour, Minglu Chen y David S.G. Goodman (Eds.) - Cornejo, Romer (México y la Cuenca del Pacífico, 2015)
Reseña del libro: Minglu Chen y David S. G. Goodman (Eds.), Cheltenham, RU y Northhampton, MA, The University of Sydney, 2013.